Morphological and biochemical changes of lymphatic vessels in the soleus muscle of mice after hindlimb unloading. Issue 5 (28th August 2021) - Kawashima, Takafumi; Ji, Rui‐Cheng; Itoh, Yuta; Agata, Nobuhide; Sasai, Nobuaki; Murakami, Taro; Sokabe, Masahiro; Hamada, Fumihiko; Kawakami, Keisuke
Abstract: Introduction/Aims: Lymphatic vessels are responsible for the removal of metabolic waste from body tissues. They also play a crucial role in skeletal muscle functioning thorough their high‐energy metabolism. In this study we investigated whether disuse muscle atrophy induced by hindlimb unloading is associated with an alteration in the number of lymphatic vessels and differential expression of lymphangiogenic factors in the soleus muscle. Methods: Male C57BL/6 mice were subjected to tail suspension (TS) for 2 or 4 weeks to induce soleus muscle atrophy. After TS, lymphatic and blood capillaries in the soleus muscle were visualized and counted by double staining with LYVE‐1 and CD31. The protein and mRNA levels of vascular endothelial growth factor (VEGF)‐C, VEGF‐D, and vascular endothelial growth factor receptor‐3 were measured by Western blotting and real‐time reverse transcript polymerase chain reaction, respectively. Results: TS for 2 weeks resulted in a significant decrease in the number of blood capillaries compared with controls. However, there was no significant change in the number of lymphatic capillaries. By contrast, TS for 4 weeks resulted in a significant decrease in the number of lymphatic and blood capillaries. We observed a significant decrease in the mRNA levels of VEGF‐C and VEGF‐D in mice subjected to TS for 4 weeks. Discussion: The decrease of intramuscular lymphatic vessels may a crucial role in the process of muscle atrophy.